Analisis Pelanggaran AMDAL Pada Industri Nikel di Indonesia serta Implikasi Terhadap Ekosistem dan Masyarakat Lokal - Arifin, Arifin; Imelda, Dhea Gita; Mutowali, Zhafira Alesha; Sugiarti, Sugiarti; Khasanah, Julia Siti Nur (DPPM Universitas Pelita Bangsa, 2025)
In the context of Indonesia, the mining industry, especially nickel, contributes greatly to the country's wealth. However, this activity often causes environmental and social problems, especially if environmental management is not in accordance with the Environmental Impact Analysis (Amdal). Amdal is important to identify negative impacts on the community and environment around the mine. The process includes evaluating water and air quality and their impacts on flora, fauna, and the socio-economic life of the local community. Many Amdal violations occur due to lack of supervision, inappropriate documents, and negligence of procedures. These violations have a major impact on people's lives and cause water pollution, deforestation, and the risk of natural disasters. This study aims to examine Amdal violations in the nickel industry and their impacts on local communities and ecosystems. The method used is normative juridical, with an analysis of laws and regulations related to Amdal, to provide recommendations for more sustainable nickel resource management